The Effect of Continuous Care Model on Surgical Site Infection in Patients Undergoing Spine Surgery: A QuasiExperimental Study. - Faghani, Fatemeh; Anboohi, Sima Zohari; Pazokian, Marzieh; Nasiri, Malihe (Journal of Evidence-based Care, 2024)
Background: Surgical site infection is an irreversible complication of spine surgery. Postoperative care instructions are of utmost significance and can decrease surgical complications, including surgical site infection. Aim: The present study was performed with aim to evaluate the impact of the continuous care model on surgical site infection in patients undergoing spine surgery. Method: This quasi-experimental study was conducted on seventy spine surgery patients referred to a teaching hospital in Tehran, Iran. The sampling process lasted from June 1 until November 30, 2022.The patients were assigned into two equal groups. The intervention involved education to patients undergoing spine surgery from admission until four weeks post-discharge based on a fourstage continuous care model. Bluebelle Wound Healing Questionnaire (BWHQ) was completed in both groups four weeks after discharge. Results: Despite the non-significant statistical difference in demographic and clinical information between the two groups, the mean total score of post-intervention infection was 9.37±5.93 in the control group and 2.65±1.43 in the intervention group. This finding indicates a significant reduction in surgical site infection in the intervention group compared to the control group (p<0.001). Implications for Practice: This study suggests that patient education based on the continuous care model following spine surgery is effective in decreasing surgical complications, specifically surgical site infection in these patients. Thus, the design and implementation of such postoperative care models are recommended for patients undergoing spine surgery.